Rare and endangered species of animals and plants, as objects of legal protection (Journal of actual problems of jurisprudence, 2019)
As a result, the number of many rare and endangered species of plants and animals living on the territory ofthe Republic of Kazakhstan, as statistics, has been steadily declining. Environmental Code of the Republicof Kazakhstan in its flora species diversity in all areas of growth is defined as an independent object of legalprotection. However, the Forest Code of the Republic of Kazakhstan regulates only certain relationshipsprotection and use of the plant world. And as we noted earlier, the forest is the only part of the plantworld. Thus, we can conclude that the national legislation of Kazakhstan settled the issue only in respectof forest vegetation in this regard, there is need for training and the adoption of the Law of the Republic ofKazakhstan "On Flora".Keywords: Rare and endangered species of plants, protection, environment, flora, fauna.